Pengaruh Bauran Pemasaran Terhadap Citra dan Keputusan Menginap Wisatawan di Hotel Bagus Jati, Ubud - Pemayun, Tjok Istri Indriyanti; Suryawardani, I Gst Ayu Oka; Wiranatha, Agung Suryawan (Jurnal Master Pariwisata (JUMPA), 2020)
Bagus Jati Hotel is one of the accommodations in Bali which is favoured by tourists, located in Ubud, Gianyar Regency. The imagery of Bagus Jati Hotel is the consideration for tourists to decide whether they want to stay or not. The imagery can be measured through the perceptions of tourists by assessing the marketing strategy which has been applied. The aim of the studys is to identify the indicators which form the Marketings Mix variables that influence the imagery and decision of tourists staying in Bagus Jati Hotel. The study uses quantitative methods which are supported by qualitative data. The study was conducted at Bagus Jati Hotel with correspondents of 100 tourists who were being staying there. The questionnaire questioned 19 indicators and literature reviews to support the results of statistical analysis. The validity and reliability tests of the data produced 17 valid and reliable indicators. Afterward the analysis of the Structurals Equations Model was conducted by using the Smarts_PLS Version 3.0 program. The results of the analysis resulted that: 1) A simultaneously Marketing Mix has a significant effect on imagery, 2) Marketing Mixed has a significant effect on tourist decisions to stay overnight, 3) Imagery has a significant effect on purchasing decisions. Keywords: Marketing Mix, Imagery, Purchasing Decision, Consumer Behaviour